Imaging in gynecological disease (15): clinical and ultrasound characteristics of uterine sarcoma. (7th October 2019) - Ludovisi, M.; Moro, F.; Pasciuto, T.; Di Noi, S.; Giunchi, S.; Savelli, L.; Pascual, M. A.; Sladkevicius, P.; Alcazar, J. L.; Franchi, D.; Mancari, R.; Moruzzi, M. C.; et al.
ABSTRACT: Objective: To describe the clinical and ultrasound characteristics of uterine sarcomas. Methods: This was a retrospective multicenter study. From the databases of 13 ultrasound centers, we identified patients with a histological diagnosis of uterine sarcoma with available ultrasound reports and ultrasound images who had undergone preoperative ultrasound examination between 1996 and 2016. As the first step, each author collected information from the original ultrasound reports from his/her own center on predefined ultrasound features of the tumors and by reviewing the ultrasound images to identify information on variables not described in the original report. As the second step, 16 ultrasound examiners reviewed the images electronically in a consensus meeting and described them using predetermined terminology. Results: We identified 116 patients with leiomyosarcoma, 48 with endometrial stromal sarcoma and 31 with undifferentiated endometrial sarcoma. Median age of the patients was 56 years (range, 26–86 years). Most patients were symptomatic at diagnosis (164/183 (89.6%)), the most frequent presenting symptom being abnormal vaginal bleeding (91/183 (49.7%)). Patients with endometrial stromal sarcoma were younger than those with leiomyosarcoma and undifferentiated endometrial sarcoma (median age, 46 years vs 57 and 60 years, respectively). According to the assessment by the original ultrasound examiners, the median diameter of the largest tumor was 91 mm (range, 7–321 mm). Visible normal myometrium was reported in 149/195 (76.4%) cases, and 80.0% (156/195) of lesions were solitary. Most sarcomas (155/195 (79.5%)) were solid masses (> 80% solid tissue), and most manifested inhomogeneous echogenicity of the solid tissue (151/195 (77.4%)); one sarcoma was multilocular without solid components. Cystic areas were described in 87/195 (44.6%) tumors and most cyst cavities had irregular walls (67/87 (77.0%)). Internal shadowing was observed in 42/192 (21.9%) sarcomas and fan‐shaped shadowing in 4/192 (2.1%). Moderate or rich vascularization was found on color‐Doppler examination in 127/187 (67.9%) cases. In 153/195 (78.5%) sarcomas, the original ultrasound examiner suspected malignancy. Though there were some differences, the results of the first and second steps of the analysis were broadly similar. Conclusions: Uterine sarcomas typically appear as solid masses with inhomogeneous echogenicity, sometimes with irregular cystic areas but only very occasionally with fan‐shaped shadowing. Most are moderately or very well vascularized. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.